Political efficacy and familiarity as predictors of attitudes towards electric transmission lines in the United States. (July 2016) - Joe, Jeffrey C.; Hendrickson, Kelsie; Wong, Maria; Kane, Stephanie L.; Solan, David; Carlisle, Juliet E.; Koehler, David; Ames, Daniel P.; Beazer, Robert
Abstract: Public opposition to the construction (i.e., siting) of new high voltage overhead transmission lines is not a new or isolated phenomenon. Past research has posited a variety of reasons, applied general theories, and has provided empirical evidence to explain public opposition. The existing literature, while clarifying many elements of the issue, does not yet fully explain the complexities underlying this public opposition phenomenon. The current study demonstrated how two overlooked factors, people's sense of political efficacy and their familiarity (i.e., prior exposure) with transmission lines, explained attitudes of support and opposition to siting new power lines.